Effects of Climate Change Across Ocean Regions - Ove Hoegh-Guldberg (Frontiers Research Topics, 2018)
The IPCC Fifth Assessment Report (AR5) highlighted that conditions within Earth's ocean are changing more rapidly than any of the time during the past 65 million years, and as a consequence, major changes are occurring in natural and human systems. While this major report as enhanced our understanding of the complexity of ocean issues, we propose this research topic as an opportunity to expand discussion on past, present and future changes across oceans regions.